PENGARUH PERSEPSI SUAMI TENTANG ALAT KONTRASEPSI DAN KETERLIBATAN ISTERI DALAM PENGAMBILAN KEPUTUSAN TERHADAP KEJADIAN UNMET NEED KB PADA PASANGAN USIA SUBUR (PUS) DI KECAMATAN BENJENG KABUPATEN GRESIK - Nur Hasanah (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2016)
Unmet need for family planning was a phenomenon that was still going on, especially in developing countries. Figures unmet need was defined as the percentage of women of childbearing age (15-49 years) were married who did not want to have any more children or wanted to delay the next birth but did not use a tool / method of contraception. This study purposed to analyze the Influence Perceptions About Contraception husband and wife Involvement in Decision Making of Genesis Unmet Need KB at Fertile Age Couple in District Benjeng. This research was an observational analytic study design Case Control Study. A large sample of 36 respondents that was couples of childbearing age were selected by random cluster sampling using primary data using questionnaires. Data analysis was conducted using Multiple Logistic Regression. The results showed the husband's perception about the tools contraception with p-value = 0.004 (p <0.05) with OR = 0.110, and there were several variables that were not significant with the age variable p-value = 0.998 (p> 0.05), revenue with p-value = 0.996 (p> 0.05), work with p-value = 0.995 (p> 0.05), the number of children living p-value = 0.997 (p> 0.05), education p- value = 1.000 (p> 0.05), giving KIE p-value = 0.998 (p> 0.05) and the wife's involvement in decision-making with a p- value = 0.997 (p> 0.05). In this study it can be concluded that the unmet need for family planning was influenced by the perception husband about contraception. Recommendations from the study were services / agencies such as BKKBN needed to keep an eye on areas of high unmet need and prone areas of unmet need, improved program performance of health workers in providing knowledge to change people's attitudes, maximizing performance Field Officer of Family Planning and disseminated family planning programs to EFA and the wider community. Increased understanding of the benefits of family planning to join the wider community by improving the quality of service delays and information, education and communication (IEC) on the importance of birth control for the welfare of society